1360 Differences between peritoneal and pleural mesothelioma in lombardy, italy. (24th April 2018) - Consonni, D; Mendola, M; Dallari, B; Sokooti, M; Tabibi, R; Callegari, R; Riboldi, L; Mensi, C
Abstract : Introduction: Asbestos is the main risk factor for development of both peritoneal (PEM) and pleural (PLM) mesothelioma, but characteristics of this two diseases and their association with asbestos show some differences. We examined characteristics of PEM and PLM in Lombardy, Italy, the most populated (currently, 10 million residents) and industrialised Italian region. Methods: The RML, established in 2000, is a population-based registry which records all cases of mesothelioma among Lombardy residents. It is part of a national network of mesothelioma registries (ReNaM). Notification of mesothelioma cases is compulsory by law. Additional sources of mesothelioma cases include hospital admission, mortality, occupational diseases, and pathology databases. Verified mesothelioma cases are interviewed about past asbestos exposure using a standardised questionnaire. For this study, from the RML database we selected PEM and PLM cases diagnosed in 2000–2014. We investigated asbestos exposure, presence of asbestosis or pleural plaques, and past employment in economical sectors. Results: We identified 300 PEM and 5, 011 PLM cases. Incidence rates (per 1.000.000 person-years, world standardised) of PEM were 2.4 (men) and 1.7 (women), compared with 52.4 and 19.9 for PLM. Asbestosis (both genders) and pleural plaques (men) were more frequent among PEM cases. Occupational asbestos exposure was similar in PEM and PLM cases. We found higher proportions of PEM employed in the asbestos cement production. Conclusion: The higher frequency of pleural plaques in PEM cases and the similar frequency of past occupational asbestos exposure confirm the association between asbestos exposure and peritoneal mesothelioma. The higher proportions of asbestosis and of past employment in the asbestos-cement sector among PEM cases suggest a possible role of high exposures to asbestos in the peritoneal mesothelioma genesis.